2021
DOI: 10.3390/nu13051599
|View full text |Cite
|
Sign up to set email alerts
|

Trends in Eating Habits and Body Weight Status, Perception Patterns and Management Practices among First-Year Students of Kaunas (Lithuania) Universities, 2000–2017

Abstract: Students’ transition from high school to university is accompanied by lifestyle changes. This study aimed to assess trends in students’ body weight status, perception, management practices and eating habits from 2000 to 2017. Three cross-sectional surveys were carried out among the first-year students of five Kaunas (Lithuania) universities in 2000, 2010 and 2017. The self-administered questionnaires were filled in during lectures. Altogether, 3275 students aged 20.0 (1.5) years participated in the survey. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 40 publications
0
8
0
Order By: Relevance
“…To our knowledge, this investigation marks the first attempt to explore the link between body weight perception and intuitive eating. Among students who viewed themselves as overweight or obese, there was a heightened inclination towards pursuing weight loss compared to those who regarded themselves as just the right weight, including instances of misperception regarding body weight ( 32 ). Those perceiving themselves as overweight tended to take various actions to achieve the desired weight loss.…”
Section: Discussionmentioning
confidence: 99%
“…To our knowledge, this investigation marks the first attempt to explore the link between body weight perception and intuitive eating. Among students who viewed themselves as overweight or obese, there was a heightened inclination towards pursuing weight loss compared to those who regarded themselves as just the right weight, including instances of misperception regarding body weight ( 32 ). Those perceiving themselves as overweight tended to take various actions to achieve the desired weight loss.…”
Section: Discussionmentioning
confidence: 99%
“…The first year is an especially critical period for the onset of pathological or disordered eating patterns. The increase in independence and responsibilities, as well as questions over personal identity all contributed in part to the pathological eating patterns [ 44 , 45 ].…”
Section: Introductionmentioning
confidence: 99%
“…First-year students are a dynamic group that experiences many challenges, changes, and opportunities during their transition to higher education. Previous studies have identified unhealthy shifts in their dietary habits and physical activity, linking the changes with weight gain [ 1 , 2 , 3 ]. In Lithuania, the prevalence of overweight and obesity increased among first-year male students (from 11.3% in 2000 to 24.3% in 2017) and female students (from 5.2 to 9.6%) [ 3 ].…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have identified unhealthy shifts in their dietary habits and physical activity, linking the changes with weight gain [ 1 , 2 , 3 ]. In Lithuania, the prevalence of overweight and obesity increased among first-year male students (from 11.3% in 2000 to 24.3% in 2017) and female students (from 5.2 to 9.6%) [ 3 ]. The COVID-19 pandemic could potentially have exacerbated these shifts.…”
Section: Introductionmentioning
confidence: 99%